Characterization of Acute Cellular Rejection in the Different Layers of Rat Transplanted Intestines. (July 2018) - Stringa, Pablo; Romanin, David; Lausada, Natalia; Gobi, Rodrigo Papa; Vecchio, Leandro; Gondolesi, Gabriel; Rumbo, Martin
Abstract : Introduction: Intestinal transplantation (IT) faces many challenges, among them, the necessity to understand and detect rejection processes. Rodent models of IT are used to provide evidence for intervention strategies as well as improve knowledge of IT biology. Our aim was to determine the kinetics of small bowel rejection with emphasis in the characterization of acute cellular rejection (ACR) in the different layers of the graft since most of the information coming from the clinics is on mucosal layer, the only one that is accessible by endoscopic biopsies. Methods: Allogeneic (ALLO) heterotopic IT in rats was performed following standard procedure. ACR was diagnosed by H-E staining analysis. Also, real-time PCR from microdissected samples (epithelial, muscular and serosa layer) and whole graft to determine gene expression was performed at 5 and 10-12 postoperative days (POD). An Isogenic IT group was performed as a control. Results: ACR was observed since 5 POD in ALLO group with mild rejection as the most characteristic grade. Severe ACR was diagnosed in all ALLO samples at 10-12 POD. Descriptive analysis showed a well-preserved architecture at 5 POD; confluent and loose apoptotic cells in the intestinal epithelium and perivascular infiltrate in all layers were evident. At 10-12 POD, significant cellular infiltrate, epithelial damage, ulcers and an increase of apoptotic cells were observed. Muscular and serosa layers showed inflammatory cell infiltrate and intercellular edema. At 5 POD, some markers were consistently increased in ALLO groups such as CXCL10 that showed a 120 ± 80-fold increase compared with nontransplanted tissue. Furthermore, IFNg and IDO showed a trend to be increased at these time points. Remarkably, other inflammation-related genes, such as CXCL1 and IL6 showed consistent increase in ALLO groups at 10-12 POD, when severe ACR was established. When a principal component analysis of the overall gene expression markers was performed, ALLO group at 10-12 POD clearly separated from the other conditions. The analysis of gene expression at different layers of the graft was coincident with whole tissue biopsies: higher levels of IL6 and CXCL1 were observed in ALLO groups at 10-12 POD with important activation of this response in serosa and muscular layer. Interestingly, IL22 expression was only measurable in epithelial layer in ALLO groups at 10-12 POD, indicating ACR-induced expression in this compartment. Serosa layer showed some of the highest relative increases in proinflammatory gene expression also in ALLO groups at 10-12 POD. Conclusion: Although in the clinic mucosal rejection has been extensively characterized, in our animal model we could document that all graft layers are affected by ACR since the initial stages. Serosa and muscular layer show high expression of proinflammatory markers, with differential expression of IL22 in the epithelial compartment. This information could be useful in the search for early biomarkers of ACR.